2019
DOI: 10.3390/medicina55100694
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Cardiovascular and All-Cause Mortality with Metabolic Syndrome in Hemodialysis Patients: A Prospective Single-Center Study

Abstract: Background and objectives: Metabolic syndrome (MetS) is a cluster of risk factors, such as abdominal obesity, insulin resistance, dyslipidemia and hypertension, that together increase the risk of cardiovascular disease. Chronic hemodialysis (HD) patients have multiple comorbidities and many metabolic disorders, causing the frequent occurrence of metabolic syndrome. The goal of this study was to assess the prevalence of MetS in HD patients, and its association with all-cause and cardiovascular (CV) mortality. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
2
1
1
Order By: Relevance
“…18,19 In the present meta-analysis, our pooled data showed that IL-6 could forecast all-cause mortality risk in dialysis patients, which could be explained as follows: (1) increased IL-6 indicates an upregulation of inflammatory status in dialysis patients, which could be attributed to infection (including catheter-related infection, peritonitis, bloodstream infection, and so on), metabolic syndrome, and severe pneumonia; these factors could lead to mortality in dialysis patients. [50][51][52][53][54] (2) IL-6 is related to cardiovascular mortality, as shown in a previous analysis, which is also a strong contributor to all-cause mortality. Therefore, higher IL-6 levels were associated with elevated all-cause mortality in dialysis patients in our pooled analysis.…”
Section: Discussionsupporting
confidence: 61%
“…18,19 In the present meta-analysis, our pooled data showed that IL-6 could forecast all-cause mortality risk in dialysis patients, which could be explained as follows: (1) increased IL-6 indicates an upregulation of inflammatory status in dialysis patients, which could be attributed to infection (including catheter-related infection, peritonitis, bloodstream infection, and so on), metabolic syndrome, and severe pneumonia; these factors could lead to mortality in dialysis patients. [50][51][52][53][54] (2) IL-6 is related to cardiovascular mortality, as shown in a previous analysis, which is also a strong contributor to all-cause mortality. Therefore, higher IL-6 levels were associated with elevated all-cause mortality in dialysis patients in our pooled analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Also supporting studies made in [9,10,21,24,26], dry weight, BMI, waist circumference, serum triglycerides were significantly higher and HDL-C levels were lower in patients with metabolic syndrome than other groups. As in this study, BMI is also high in patients with metabolic syndrome (p < 0.05), is an independent predictor of metabolic syndrome in hemodialysis patients without diabetes and dyslipidemia [9,15,22,24,27]. These discrepancies in the results of different studies could be attributed to the different populations and healthcare settings between these studies and the current study.…”
Section: Discussioncontrasting
confidence: 46%
“…отметили, что основными причинами, приводящими к снижению чувствительности к инсулину у пациентов с ХБП, являются: анемия, воспаление, оксидативный стресс, дефицит витамина D, метаболический ацидоз, уремическая интоксикация, нездоровый образ жизни [11]. У гемодиализных больных наличие ИР значительно увеличивает частоту возникновений сердечно-сосудистых событий [14,15]. M. Guthoff и соавт.…”
Section: особенности метаболизма глюкозы и интерпретации значений био...unclassified